Micro and Martsolf syndromes in 34 new patients: Refining the phenotypic spectrum and further molecular insights. Issue 5 (20th October 2020) - Abdel‐Hamid, Mohamed S.; Abdel‐Ghafar, Sherif F.; Ismail, Suzan R.; Desouky, Lubna M.; Issa, Mahmoud Y.; Effat, Laila K.; Zaki, Maha S.
Abstract: Micro and Martsolf syndromes are rare clinically and genetically overlapping disorders caused by mutations in RAB3GAP1, RAB3GAP2, RAB18 and TBC1D20 genes . We describe 34 new patients, 27 with Micro and seven with Martsolf. Patients presented with the characteristic clinical manifestations of the two syndromes, including postnatal microcephaly, congenital cataracts, microphthalmia, optic atrophy, spasticity and intellectual disability. Brain imaging showed in the majority of cases polymicrogyria, thin corpus callosum, cortical atrophy, and white matter dysmyelination. Unusual additional findings were pectus excavatum (four patients), pectus carinatum (three patients), congenital heart disease (three patients) and bilateral calcification in basal ganglia (one patient). Mutational analysis of RAB3GAP1 and RAB3GAP2 revealed 21 mutations, including 14 novel variants. RAB3GAP1 mutations were identified in 22 patients with Micro, including a deletion of the entire gene in one patient. On the other hand, RAB3GAP2 mutations were identified in two patients with Micro and all Martsolf patients. Moreover, exome sequencing unraveled a TBC1D20 mutation in an additional family with Micro syndrome. Our results expand the phenotypic and mutational spectrum associated with Micro and Martsolf syndromes. Due to the overlapped severities and genetic basis of both syndromes, we suggest to be comprehended as one entity "Micro/Martsolf spectrum" or "RAB18 deficiency." Abstract :